Redistributing the poor: jails, hospitals, and the crisis of law and fiscal austerity - Lara-Millán, Armando (Oxford University Press, 2021)
"This book argues that we have drastically misunderstood the changes taking place in our nation's largest jails and public hospitals. And more generally, the way that states govern urban poverty at the turn of the 21st century. It is widely believed that because we as a society have divested in public health the sick and poor now find themselves subject to powerful criminal justice institutions. Rather than focus on the underinvestment of health and overinvestment of criminal justice, this book argues that the fundamental problem of the state is a persistent crisis between budgetary catastrophe and expansive new legal rules. Redistributing the Poor pushes us to think about the circulation of people for the purposes of generating absent revenue, absolving new legal demands, and projecting illusions that crisis have been successfully resolved. This book takes us into the heart of the state: the day-to-day operations of the largest hospital and jail system in the world. It is only by centring the states use of redistribution that we can understand how certain forms of social suffering-the premature death of mainly poor, people of color-are not a result of the state's failure to act, but instead the necessary outcome of so-called successful policy."